2014
DOI: 10.1371/journal.pone.0099920
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Collagen Peptides Compounds Promote the Proliferation and Differentiation of MC3T3-E1 Pre-Osteoblasts

Abstract: ObjectiveCollagen peptides (CP) compounds, as bone health supplements, are known to play a role in the treatment of osteoporosis. However, the molecular mechanisms of this process remain unclear. This study aimed to investigate the effects of bovine CP compounds on the proliferation and differentiation of MC3T3-E1 cells.MethodsMouse pre-osteoblast cell line MC3T3-E1 subclone 4 cells were treated with bovine CP compounds. Cell proliferation was analyzed by MTT assays and the cell cycle was evaluated by flow cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 30 publications
7
46
0
Order By: Relevance
“…The formation of osteoblast mineralization nodules reflects the ability of bone cell differentiation. Results here showed that different molecular weight collagen peptides can increase the OC level in MC3T3-E1 cells and mineralization of osteoblasts, similar as our previous results [21].…”
Section: Discussionsupporting
confidence: 92%
“…The formation of osteoblast mineralization nodules reflects the ability of bone cell differentiation. Results here showed that different molecular weight collagen peptides can increase the OC level in MC3T3-E1 cells and mineralization of osteoblasts, similar as our previous results [21].…”
Section: Discussionsupporting
confidence: 92%
“…These results indicate that Pro-Hyp can promote the differentiation of osteoblasts by upregulating gene expression of Runx2 and Osterix. Previous reports have shown that treatment with crude CP increases the expression of the Runx2 and the Col1a1 genes in osteoblastic cells [13,14]. The regulation by Pro-Hyp in MC3T3-E1 cells would explain a mechanism of the protective effect of CP in bone metabolism.…”
Section: Discussionmentioning
confidence: 88%
“…Previous reports have shown that crude CP stimulates the proliferation of osteoblast cells. In one previous report, crude CP was used that may include various collagen-derived di-, tri-, and oligo-peptides such as Pro-Hyp, Pro-Hyp-Gly, Hyp-Gly, or Ala-Hyp [12][13][14]. It is speculated that these collagen-derived peptides, except Pro-Hyp, have the ability to enhance osteoblast proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plinia peruviana extract having antioxidative activities was reported to demonstrate the potential for stimulation of L929 cell proliferation and wound healing properties (Pitz et al, 2016). Liu et al (2014) found that collagen peptides could promote osteoblast proliferation by inducing cell cycle arrest in G2/S phase (DNA synthesis) performed by flow cytometry scanning. In addition, VitC has been known for promoting skin health by inducing the synthesis of a normal mature collagen network by maintaining optimal lysyl and prolyl hydroxylase activity, two essential enzymes in the collagen biosynthesis pathway (Boyera et al, 1998).…”
Section: Effect Of Hc Vitc and Their Mixtures On Cell Proliferation mentioning
confidence: 99%